Efektivitas Crisis Management Initiative (CMI) Dalam Upaya Membangun Perdamaian Pasca Memorandum Of Understanding (MoU) Helsinki Di Aceh - Muhammad Fahry; Ahmad Fuadi (Global Political Studies Journal, 2020)
This research discusses the effectiveness of the Crisis Management Initiative (CMI) in efforts to build peace after the Helsinki MoU in Aceh. The involvement of CMI in the Aceh conflict was an achievement that led Martti Ahtisaari to win the Nobel Peace Prize in 2008. The condition of peace after the signing of a memorandum of understanding was the responsibility of all related parties including CMI. On this basis, CMI pursued a peace project to build peace after the Helsinki MoU. This research uses the perspective of Pluralism, Effectiveness theory, and International Organization theory. In carrying out its role, CMI as an international conflict resolution organization does it very well and in accordance with the values of an international organization. The role of CMI in Aceh's peace resulted in a sustainable peace process that continues to this day. CMI skills by involving all elements and local capacities make CMI's role effective. The effort made a new enthusiasm for all parties to be able to realize immediately all the points of the Helsinki MoU to create sustainable peace in Aceh and remain within the frame of the Republic of Indonesia.